Pengaruh Motivasi Kerja Dan Pengembangan Karir Terhadap Kepuasan Kerja Pegawai Pada Perusahaan Daerah Air Minum (PDAM) Balikpapan - Sri Wahyuni Suwartiningsih; Joko Sabtohadi; Farida Mallu (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2019)
Abstract:Regional Water Company (PDAM) of Balikpapan City realizes the importance of the role of employees who are the main movers for the smooth implementation of the tasks of the company. Because it needs to be maintained and maintained by fulfilling their needs and desires.The multiple regression results show: Y = 6.923 + 0.264 X1 + 0.410 X2 + ei. The equation of the multiple regression analysis model shows the influence of each independent variable on the dependent variable, which is indicated by the regression coefficients of each independent variable. Regression coefficients of independent variables which are positive means that the independent variable has a direct effect on employee job satisfaction and vice versa.Simultaneously the independent variables of work motivation and career development have a significant effect on employee job satisfaction where the value of F Ming = 35.947 is greater than F label = 3.20 at the real level below 5%. Then it can be concluded that the first hypothesis proposed in this study is proven to be true, namely, it is assumed that simultaneously work motivation and career development have a significant effect on employee job satisfaction in Balikpapan Regional Water CompanyPartially the dominant influence on employee job satisfaction is career development, where the value of t count is 2.719> t table is 1.69973 with the value of Sig t = 0.009 <0.05. It means that the second hypothesis proposed in this study is also proven to be true, that is, it is assumed that career development has a significant and dominant effect on employee job satisfaction in Balikpapan Regional Water Company (PDAM)Keywords: Work Motivation, Work Achievement and Work Satisfaction